Early life 1000 days: opportunities for preventing adult diseases - Juan, Juan; Yang, Huixia (Chinese medical journal, 2021)
According to a population-based cohort study among >6.4 million women aged 20 to 49 years in China, the awareness rate of blood glucose levels and diabetes mellitus status among reproductive-age women before pregnancy is extremely low, and the management of pregestational diabetes mellitus (GDM) remains unsatisfactory, even in patients who are aware of their diabetes mellitus status, which may cause serious adverse maternal and perinatal outcomes. In China, a GDM One-Day Care Program was launched in May 2011 at Peking University First Hospital to educate GDM patients on the basic knowledge of GDM, weight management, medical nutrition therapy, physical exercise advice, and blood glucose self-monitoring methods by professional physicians, nurses, as well as clinical nutritionists. [...]more attention should also be paid to postnatal period to promote long-term health. [...]the postnatal care rate is relatively low in China currently, which might owe to multiple barriers, such as lack of self-efficacy and social support, as well as professional knowledge among health providers. [...]healthcare providers should cooperate to provide more support for postnatal care.